Application of the technology- organization- environment framework on big data analytics deployment in manufacturing and service / Sharina Tajul Urus ... [et al.] - Tajul Urus, Sharina; Rahmat, Fahzilah; Othman, Intan Waheedah; Syed Mustapha Nazri, Sharifah Nazatul Faiza; Abdul Rasit, Zarinah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
The rising demand for Big Data Analytics (BDA) is essential for maintaining market competitiveness, providing valuable insights and opportunities for smarter business decisions and efficient operations. While big data offers several benefits, organisations in Malaysia are still in the infancy stage of adopting the technology. This study aimed to examine the determinant factors of Technology-Organization-Environment (TOE) in relation to the Big Data Analytics deployment by Malaysian organizations. Based on the TOE Framework, a survey questionnaire was distributed via email and google form to the existing companies in the manufacturing and service industries in Klang Valley. A total 116 responses were received. The study revealed that the deployment of BDA in Malaysia's manufacturing and service sectors was influenced by seven determinant factors (relative benefit, compatibility, organisational resources, top management support, competition intensity, regulatory support, and external support), while technological complexity and organisation size were not significant. Findings from the study provide a comprehensive analysis of factors influencing BDA technology adoption, utilizing the TOE as the comprehensive model to assist practitioners in making informed decisions. The study extended the utilisation of the TOE framework from the wider dimension that emphasised the technological aspect such as technology readiness, the usefulness of the technology, the complexity and technology compatibility within the organisation. From the practical perspective, this study provides an avenue for practitioners to learn the fundamentals of BDA adoption in various industries resulted in time and cost saving prior to effective decision making. The findings also highlight the government's crucial role in facilitating businesses' implementation of BDA, offering suggestions on incentives, precise standards, and lenient rules.